PENGARUH MANAJEMEN FASILITAS PERPUSTAKAAN DAN MANAJEMEN PELAYANAN PERPUSTAKAAN TERHADAP MINAT BACA PESERTA DIDIK - Fiqriansyah, Nanda (Universitas Nurul Jadid, 2021)
This study aims to find out about; 1) the influence of library facility management on students' reading interest, 2) the influence of library service management on students' reading interest, 3) the influence of library facility management and library service management on students' reading interest at SMAN 1 Pringsewu. This study used a quantitative approach with a population of 611 students and a sample of 242 students. The data in this study were analyzed using simple linear regression analysis and multiple linear regression analysis using statistical software. The results showed that; 1) the significance value of the library facility management X1 variable was 0.000 less than 0.05, 2) the significance value of the library service management X2 variable was 0.000 less than 0.05, and 3) the significance value of the X1 variable facility management variable library, namely 0.000 and X2 library service management which is 0.030 less than 0.05. Can be concluded that; 1) there is a significant influence of library facility management on students' reading interest, 2) there is a significant influence of library service management on students' reading interest, 3) there is a significant influence of library facility management and library service management on students' reading interest in SMAN 1 Pringsewu.